Poly‐L‐lysine/hyaluronan nanocarriers as a novel nanosystem for gene delivery. (29th April 2022) - Souri, Masoumeh; Bagherzadeh, Mohammad Aref; Mofazzal Jahromi, Mirza Ali; Mohammad‐Beigi, Hossein; Abdoli, Amir; Mir, Hamed; Roustazadeh, Abazar; Pirestani, Majid; Sahandi Zangabad, Parham; Kiani, Jafar; Bakhshayesh, Amirmahmoud; Jahani, Mehdi; et al.
Abstract: The present research comes up with a novel DNA‐loaded poly‐L‐lysine (PLL)/hyaluronan (HA) nanocarrier (DNA‐loaded PLL/HA NCs) for gene delivery applications, as a promising candidate for gene delivery into diverse cells. A straightforward approach was employed to prepare such a nanosystem through masking DNA‐loaded PLL molecules by HA. Fourier‐transform infrared (FTIR) spectroscopy, dynamic light scattering (DLS), field emission‐scanning electron microscopy (FE‐SEM) and transmission electron microscopy (TEM) were used to analyse the interaction of the molecules as well as the physicochemical properties of the NCs. The NCs showed a negative charge of –24 ± 3 mV, with an average size of 138 ± 6 nm, in an ellipsoid‐shape with smooth surfaces. The DNA loading efficiency (LE) measured by DNA absorbance was around 95 %. The MTT assay showed that the developed NCs are non‐toxic to the cells. Furthermore, the uptake of the DNA‐loaded PLL/HA NCs by the human embryonic kidney (HEK)‐293T cells was evaluated by a flow cytometry method, and demonstrated high potential cellular uptake over 90% for transferring the gene to HEK‐293T cells at the optimised conditions. Therefore, the DNA‐loaded PLL/HA NCs are the potent strategy for developing nanosystems for gene delivery applications.